FINITE DIFFERENCE METHOD DETERMINATION OF THE NANO-HETERO-INTERFACE WAVE-FUNCTION ENGINEERING OF INTER-SUBBAND LASER FUNCTIONALITY - EMMANUEL A. ANAGNOSTAKIS (TASK Quarterly, 2004)
A novel LASER action nano-hetero-structure of the inter-subband, mid-infrared functionality type is designed on the basis of optically pumped dual resonant tunnelling of conductivity electrons within an appropriately energetically determined scheme of five subbands hosted by two communicating asymmetric, approximately rectangular quantum wells (QWs).